For a Relational Critical Discourse Analysis - Zarycki , Tomasz (Stan Rzeczy, 2017)
This paper proposes a relational and critical sociological perspective on discourse analysis, in particular on so-called “Critical Discourse Analysis” (CDA). The main argument of this paper is that CDA has not yet been able to turn its critical perspective towards its own field. Meanwhile, neither CDA nor other schools of discourse analysis can still pretend not to be integral parts of the system legitimizing social hierarchies in modern societies. The paper argues that discourse analysis can be seen as highly dependent on power relations, both because of its institutional positioning and because of its restricted reflexivity. A call for the development of a critical sociology of discourse analysis based on a relational approach is therefore presented. Its draft programme is largely based on inspiration from the sociology of knowledge, in particular from “the sociology of sociology” of Pierre Bourdieu.